Tubal abnormalities in patients with intrauterine adhesion: Evaluation using hysterosalpingography - Olawale, BalogunBabajide; Ademola, AdegboyegaOlukayode; Gbadebo, AwosanyaGbolahan Olusegun (Annals of African medicine, 2014)
Intrauterine adhesion (IUA) represents scar tissue inside the uterine cavity. Many patients may experience recurrent miscarriages, menstrual dysfunction, and may also be unable to achieve pregnancy. Tubal abnormalities are a significant cause of infertility in women. Hysterosalpingography (HSG) is a useful screening test for the evaluation of the uterine cavity and provides information relating to the assessment of tubal morphology and patency. The HSG radiographs of 92 patients with intrauterine adhesions, between November 2008 and October 2011, in the Lagos State University Teaching Hospital, were assessed and analyzed for tubal abnormality. Out of the 92 patients studied, 12 (13.04%) were diagnosed with primary infertility, while the rest of the 80 (86.96%) were referred for secondary infertility. The age range of the patients was between 27 and 42 years, with a mean age of 34.58 ± SD years. The mean infertile period of all the study subjects was 5.78 ± SD years. The prevalence of tubal abnormalities demonstrated in the study was 67.39%. Sixty-six (71.73%) patients presented with minor adhesions, while 26 (28.27%) patients presented with moderate adhesions. Conclusion : The prevalence of tubal abnormalities demonstrated in patients with intrauterine adhesion was 67.39%.